La formación docente en la práctica de la educación inclusiva - Plúa Bonilla, Mercedes Elizabeth (2021)
Inclusion is one of the perhaps most important challenges of the current era. Inequality has been a great problem in societies historically, because it generates social exclusion. However, the emergence of the notion of diversity confers a positive and less pejorative character. Diversity is a concept that makes it possible to recognize differences as part of human reality. In this sense, UNESCO has proposed education for all as the axis and goal of democratic countries. In Ecuador, educational policies and legislation assume inclusive education as a mandate over all Ecuadorian education. However, teachers have not yet been sufficiently trained to have inclusive practices in the classroom and school settings…………